A Look into the Bumpy Road of US Commitment to International Environmental Law: The Case of the Paris Agreement - Manullang, Abel; Gultom, Yosua (Politeia: Jurnal Ilmu Politik, 2025)
International environmental law is one of the important pieces in the present international system. The aforementioned matter plays an important role in uniting or at least attempting to unite the many states in the world to address the environmental threat the world is being exposed to. One of them is present in the form of the Paris Agreement, a product of the United Nations Framework Convention on Climate Change (UNFCCC) concerned with the issue of climate change. Among the states in the world, the US, one of the world’s global powers, is one of its party members. The US has had a rather rocky record regarding its commitment to the Paris Agreement. A case can be made out of the Trump administration’s move to exit the Paris Agreement. However, it would soon reenter the agreement under the subsequent Biden administration. With that development in mind, the writer sets out to describe and explain why the drastic change of attitude towards the international environmental law of the Paris Agreement occurred. To that end, the writer posits how the different stances to the agreement was a result of the different interest or perspective towards the regime and climate change, as well as other matters touched upon in the paper.